1999
DOI: 10.1080/01616412.1999.11740933
|View full text |Cite
|
Sign up to set email alerts
|

Time course of IL-6 expression in experimental CNS ischemia

Abstract: Interleukin-6 (IL-6) appears to be an important modulator of the inflammatory response associated with CNS ischemia. Clinically, IL-6 values obtained in the first week post-stroke have been shown to correlate with infarct size and outcome. In this study we used a focal reversible stroke model to investigate the time course and relationship to outcome of IL-6 production in plasma, brain and CSF. Reversible middle cerebral artery occlusion or sham surgery was produced in 50 adult Swiss Webster mice by advancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 14 publications
7
33
0
1
Order By: Relevance
“…There is strong evidence implicating several inflammatory cytokines and their receptors in exacerbation of focal I/R damage, although protective effects for TNF-␣ and IL-6 also were also reported. Levels of IL-6 had a strong correlation with neurologic function and infarct size in animal experimental ischemia as well as in stroke patients (33,34). It was also demonstrated that the IL-6 system plays an important role in local inflammatory reactions by amplifying leukocyte recruitment and changing endothelial permeability (35).…”
Section: Discussionmentioning
confidence: 96%
“…There is strong evidence implicating several inflammatory cytokines and their receptors in exacerbation of focal I/R damage, although protective effects for TNF-␣ and IL-6 also were also reported. Levels of IL-6 had a strong correlation with neurologic function and infarct size in animal experimental ischemia as well as in stroke patients (33,34). It was also demonstrated that the IL-6 system plays an important role in local inflammatory reactions by amplifying leukocyte recruitment and changing endothelial permeability (35).…”
Section: Discussionmentioning
confidence: 96%
“…The concentration of IL-6 giving maximum stimulation was 2.5 ng/mL, ie, a concentration comparable to serum levels of IL-6 recorded in an in vivo experimental mouse central nervous system ischemia model. 21 Notably, exposure of Paju cells to hypoxia overnight did not, however, directly induce increased STC-1 expression (data not shown).…”
Section: Stc-1 Expressionmentioning
confidence: 99%
“…An elevated level of IL-1β can potentiate inflammation by activating microglia and induce the infiltration of peripheral leukocytes by increasing the expression of adhesion molecules on endothelial cells; these events are associated with worsening of the infarct severity and progressive neurodegeneration (81)(82)(83). In addition to its role as a pro-inflammatory mediator, IL-1β can also elevate the expression of other pro-inflammatory cytokines, such as IL-6 and TNF-α, which can be upregulated following cerebral ischemia (84).…”
Section: Role Of Cytokines In Cerebral Injury Following Ca and Resuscmentioning
confidence: 99%